2002
DOI: 10.1149/1.1502684
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Improve the Behavior of Li Electrodes in Rechargeable Lithium Batteries

Abstract: In this work we studied properties of modified lithium electrodes in an attempt to improve the high rate performance of rechargeable Li (metal) batteries containing liquid electrolyte solutions. Li (metal)- Li0.3MnO2 AA batteries with solutions containing 1,3-dioxolane (DN), LiAsF6, and a basic stabilizer became commercial several years ago but failed to compete with Li-ion battery technology because of a very limited cycle life at high charging rates. The problem relates to intensive reactions between Li d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
103
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 22 publications
2
103
0
1
Order By: Relevance
“…As to the N 1s spectra ( Supplementary Fig. 4), for both samples, the three peaks centred at 399.9, 404.3 and 408.0 eV can be assigned to N in the N-S bond, NO 2 À and NO 3 À , respectively, indicating that LiNO 3 is reduced by lithium to LiNO 2 , whereas the sulfone species in the LITFSI can be oxidized to SO 3 2 À and SO 4 2 À (identified from the S 2p spectra for both samples). The difference in the N 1s spectra of the two samples is that the N 1s signal for the SEI containing Li 2 S/Li 2 S 2 is much weaker, only slightly higher than noise level.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As to the N 1s spectra ( Supplementary Fig. 4), for both samples, the three peaks centred at 399.9, 404.3 and 408.0 eV can be assigned to N in the N-S bond, NO 2 À and NO 3 À , respectively, indicating that LiNO 3 is reduced by lithium to LiNO 2 , whereas the sulfone species in the LITFSI can be oxidized to SO 3 2 À and SO 4 2 À (identified from the S 2p spectra for both samples). The difference in the N 1s spectra of the two samples is that the N 1s signal for the SEI containing Li 2 S/Li 2 S 2 is much weaker, only slightly higher than noise level.…”
Section: Resultsmentioning
confidence: 94%
“…L ithium metal, having a high theoretical specific capacity of 3,860 mAh g À 1 and the most negative electrochemical potential among anode materials, has been considered an ideal anode in lithium battery systems over the past four decades [1][2][3][4][5][6] . The recent emerging demand for extended-range electric vehicles has stimulated the development of high-energy storage systems [7][8][9][10] , especially the highly promising lithiumsulfur and lithium-air batteries, in which lithium metal anodes are employed.…”
mentioning
confidence: 99%
“…[6][7][8] They found that there were obvious differences in the composition and thickness for the SEI films on the different planes, and deduced that solvents were preferentially reduced on the basal plane and the salt anions on the edge plane. Aurbach et al [9][10][11][12][13][14][15][16][17][18] used XPS, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive analysis by X-ray (EDAX), X-ray diffraction (XRD), and electrochemical impendence spectroscopy (EIS) etc. to systematically investigate the SEI film in different electrolytes and on different electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of this layer during prolonged cycling is regarded to be the main source of anode ageing according to many researchers. [48][49][50] As mentioned before CO 2 is an ageing product. Therefore, the cycled battery cells were expected to give rise to higher amounts of CO 2 during crushing.…”
Section: Resultsmentioning
confidence: 76%